2016
DOI: 10.4155/bio-2016-0166
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Circulating Biomarkers in Parkinson’s Disease: The Potential Use of Mirnas in A Clinical Setting

Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disorder, affecting 5% of the elderly population. PD diagnosis is still based on the identification of neuromotor symptoms although nonmotor manifestations emerge years prior to diagnosis. The discovery of biomarkers at the earliest stages of PD is of extreme interest. miRNAs have been considered potential biomarkers for neurodegenerative diseases, but only a limited number have been found to be PD related. This review focuses on the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 178 publications
0
10
0
Order By: Relevance
“…Several studies have highlighted altered levels of α-synuclein (α-syn), DJ-1, amyloid beta (Aβ) and Tau proteins in late stage, symptomatically identified PD patients compared with controls [ 12 17 ]. Nevertheless, these findings are not consistently observed in different studies [ 18 ].…”
Section: Introductionmentioning
confidence: 80%
“…Several studies have highlighted altered levels of α-synuclein (α-syn), DJ-1, amyloid beta (Aβ) and Tau proteins in late stage, symptomatically identified PD patients compared with controls [ 12 17 ]. Nevertheless, these findings are not consistently observed in different studies [ 18 ].…”
Section: Introductionmentioning
confidence: 80%
“…In our study, we analyzed total α-syn in the CSF and found it expressed in lower levels in the CSF of early stage PD patients compared to controls. Although the majority of publications support this finding, there is still conflicting data available [ 15 ]. Furthermore, different isoforms of α-syn have been investigated and proposed as potential biomarkers, including monomeric and phosphorylated forms, among others [ 9 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies have highlighted altered levels of α-syn and DJ-1 in PD patients compared with controls [ 9 14 ]. Furthermore, due to assay incompatibility and lack of standardized protocols, results are conflicting and do not show robustness for use as clinical biomarkers [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microRNA regulatory network in PD has been discussed before, particularly in the potential of miRNAs as circulating biomarkers for the diagnosis and treatment of PD (dos Santos et al, 2016 ; Ma et al, 2016 ; Marques et al, 2016 ; Mushtaq et al, 2016 ; Batistela et al, 2017 ), in PD progression (Heman-Ackah et al, 2013 ) as well as in the oxidative stress pathway (Qiu et al, 2014 ; Xie and Chen, 2016 ). However, none of these discussions emphasis on the potential of these miRNAs to differentiate the EOPD from LOPD.…”
Section: Microrna Regulatory Network In Parkinson Diseasementioning
confidence: 99%